Mối quan hệ giữa hoạt động phòng thủ dân sự với công tác quản lý tài nguyên và môi trường - Bộ Tài nguyên và Môi trường (2022)
Mối quan hệ giữa hoạt động phòng thủ dân sự với công tác quản lý tài nguyên và môi trường